Fungicidas comerciales para el control de hongos patógenos causantes de la descomposición de corona en el cultivo de banano (Musa Spp) - Marin Galarza, Pedro Pablo (2013)
This experiment was carried out on the ranch property Bertha Maria Company "MENDOZA GROUP" located in the Camarones, Province of Los Ríos, Canton Good Faith The experiment lasted approximately five weeks, we studied the response two fungicides and Magnate Mertec either alone or in combination to control crown rot of bananas in order to assess the behavior and productive capacity of banana processing plant, it was determined that all characters differed significantly for dosage effect between treatments, agreeing with González 1997 and 1993 Finlay who indicate that the crown rot is a tissue softening and browning on the cut surface of the crown, which spreads to the pedicels, each of the microorganisms that cause disease grows rapidly at tropical temperatures (between 25 ° C to 30 ° C) and decreases the rate of development at low temperatures, such as those used in transport vessels product (13.3 ° C to 13.5 ° C ). Further states that the period of time from harvest until cooling is important in the development of the disease. Reaching the lower average coverage (60%) treatment witness which showed a degree of rot quite elevated, but treatments based on Mertec and Tycoon with doses of (250 cc 80 gr) he obtained the lowest average with 1.0 mm, treatment 10 Mertec Tycoon compound dose (250 cc 80 gr) obtained an average of 1.3 of the scale mentioned above but statistically equal to 5 Tycoon (60 g) treatmentsTycoon (80 g), Mertec Tycoon (150 cc (60 g) and Tycoon (200 cc (70 g) with averages of 2.17; 1.60; 1.67 and 1.50 respectively in their ordenLa greater penetration of corona was obtained in treating witness with 4.00 mm, while treatments with Mertec dose (200 cc) and Tycoon dose (80 g) reported 1 mm presenting statistical differences. If we compare with Mertec and Tycoon combined treatments shown greater penetration of Crown rot. Within the index of maturation, the following results were obtained: the control treatment was an index of 4 (more yellow than green), the lower value was reported with Mertec dose (200 cc) and Tycoon dose (80 g) with an index (dark green) 2. It was xiv observed that Mertec dose treatment (150 cc) reported the index 5 (yellow with green dots).